Work Harassment and Resource Loss Among (Ex)partner Stalking Victims - Logan, TK (Journal of interpersonal violence, 2023)
Prior research suggests that economic abuse and work sabotage are common tactics for abusers and (ex)partner stalkers. This study examines the context and timing (i.e., during the relationship or during separation) of work harassment among women stalked by abusive (ex)partners among victims who did (n=271) and who did not (n=302) experience work losses (significant problems at work or loss of work due to the abuse/stalking) and whether work losses and non-work related resource losses were associated with current mental health symptoms. Results showed that almost half of the women in the study reported they experienced work losses because of their abusive (ex)partner. Women with work losses experienced more work harassment particularly during periods of separation. Women who experienced work losses also experienced more work harassment, separation attempts, economic control, coercive control, physical and sexual abuse, higher fear levels, and a higher number of non-work related resource losses compared to women who did not report experiencing work losses. Women with work losses experienced more symptoms of current depression, anxiety, and Post-Traumatic Stress Disorder. Further, in the multivariate analysis, non-work related resource losses were significantly and uniquely associated with current mental health symptoms. In conclusion, women being stalked by abusive (ex)partners are at significant risk of resource losses, and those losses have long term impacts on mental health suggesting that safety planning for stalking victims should include plans to protect resources as well as physical safety.